(3EfJNGH GdWHQGfis - (3CHh fYje,J (B430 (3g` s
(3ChdgG (B:s
(3CNHQfG CHh Ydi GdMSjf Hf CMeO Hf GdMSf Yf LGHQ Yf GdfHi Udi Gddg Ydjg hSde bGd (B: ( (3dGjVQ GdeQCI GdMGFV hGdLfH s
(3BNQgG (B:s
(3hEf CMOce djYed HYed Cgd GdfGQ MJi GdehJ Hjfg hHjfgG ZjQ PQGY hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B282s
Keywords: (3GdMOjK h GdeUWdMs